Scarred millennials: the impact of the great recession on earnings across demographic cohorts - Quintela, Carolina Moreira de Almeida (2022)
This work project studies the impact of the Great Recession on workers’ earnings across demographic cohorts in Portugal. Using microdata from Quadros de Pessoal from 2010 to 2019, an empirical model decomposes the effect of the unemployment rate on real earnings. Results show that Millennials were the most affected with the aftermath of the Great Recession, a one percentage point increase in the unemployment rate decreases their earnings by 0.97%. The probability of workers having open-ended employment contracts is also three times more negatively affected by unemployment in the case of Millennials than the other generations.